Cognitive Algorithms for Learning Foreign Languages: Psycholinguistics Approach - Natalia Koval (Educational Challenges, 2021)
The relevance of the undertaken research consists in considering psycholinguistics an interdisciplinary field, which studies the interrelation between mind and language. It is important to perceive learning foreign language as an act of cognition, experience, and creativity in the psycholinguistic aspect of studying. Psycholinguistics concerns with the study of the cognitive process that supports the acquisition and use of language.